The digital euro and central bank digital currencies: Beware of taking off too early - Peter Bofinger (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2024)
The paper discusses central digital currencies (CBDCs) with an analytical focus on the European Central Bank's Digital Euro (D exteuro) project, which provides a unique lens for assessing the potential and challenges of CBDCs. The paper differs from the literature on CBDCs and the D exteuro by adopting a systemic perspective that distinguishes between the role of CBDCs as a new payment object and as a new payment system based on CBDC accounts. In a worst-case scenario, the D exteuro project could be a total flop, with people not opening accounts and the system failing to compete with existing platforms. This would be in line with the dismal experience of countries that have already introduced CBDCs. In a more positive scenario, many households would open D exteuro accounts alongside commercial bank accounts, potentially reducing the dominance of US platforms. However, even in this scenario, it is unlikely that there will be significant holdings of D exteuro deposits as a means of payment, making the D exteuro payment system an inefficient and costly detour between existing commercial bank accounts. The offline version remains difficult to justify. Our CBDC tracker shows that the ECB's strong commitment to the D exteuro is unique among central banks in advanced economies. Many of them, including the Federal Reserve, currently rule out the option of a retail CBDC. Thus, the ECB's unconditional commitment to the D exteuro carries a high risk of failure. It is therefore unclear why the ECB is not considering a scheme based on the existing SEPA infrastructures.
Keywords: 330; Digital Euro; central digital currencies; CDBC; ECB